Evaluation of microcystin contamination in blue-green algal dietary supplements using a protein phosphatase inhibition-based test kit. Issue 3 (March 2018) - Marsan, David W.; Conrad, Stephen M.; Stutts, Whitney L.; Parker, Christine H.; Deeds, Jonathan R.
Abstract: The cyanobacterium Aphanizomenon flos-aquae (AFA), from Upper-Klamath Lake, Oregon, are used to produce blue-green algal (BGA) dietary supplements. The periodic co-occurrence of hepatotoxin-producing contaminant species prompted the Oregon Health Division to establish a limit of 1 μg/g microcystin (MC) for products sold in Oregon in 1997. At the federal level, the current good manufacturing practice (CGMP) regulations for dietary supplements require manufacturers establish a specification, and test, for limits on contaminants that may adulterate finished products. Despite this, several previous international surveys reported MC in BGA supplements in excess of 1 μg/g. The objectives of this study were (1) identify a reliable, easy to use test kit for the detection of MC in dried BGA materials and (2) use this kit to assess the occurrence of MC contamination in AFA-BGA dietary supplements in the U.S. A commercial protein phosphatase inhibition assay (PPIA), based on the enzyme PP2A, was found to have acceptable relative enzyme inhibition and accuracy for the majority of MC variants tested, including those most commonly identified in commercial samples, making the kit fit for purpose. Using the PPIA kit, 51% (26 of 51) distinct AFA-BGA products had MC ≥0.25 μg/g (the detection limit of the kit), 10 products had MC concentrations between 0.5 and 1.0 μg/g, and 4 products exceeded the limit (1.1–2.8 μg/g). LC-MS/MS confirmed PPIA results ≥0.5 μg/g and determined that MC-LA and MC-LR were the main congeners present. PPIA is a reliable method for the detection of MC contamination in dried BGA dietary supplements produced in the U.S. While the majority of AFA-BGA products contained ≥0.25 μg/g MC, most were at or below 1.0 μg/g, suggesting that manufacturers have adopted this level as a specification in these products; however, variability in recommended serving sizes prevented further analysis of consumer exposure based on the concentrations of MC contamination found.